Determinants of the Productivity of the Companies of the Service Sector in Ecuador, during the years 2010 2019 - Simbaña, Lizbeth (2021)
Productivity is a performance measure that allows us to know the performance of factors incorporated in the production process (Arévalo-Avecillas et al., 2018). Poor productivity is a problem not only for Ecuador but also for Latin America, this situation is the cause of the lack of socio-economic development in the region. Almost 90% of the differences in terms of per capita income in Ecuador with respect to the US is the result of low total factor productivity (CAF, 2018). Therefore, the starting point to improve it would be attributed to the fact of clarifying the panorama in relation to the use of resources, with the aim of interfering in their application. The focus of this topic is given around the service sector , since the expansion of this type of activities has introduced the need to reconsider its importance in the progress and growth of economies (Martínez Serrano & Picazo Tadeo, 2000). Considering Ecuador in 2019, the sector with the largest number of companies is services, covering 44% of them. At the same time, it is classified as one of the main economic sectors in terms of; to the percentage of sales, which reach 25% with respect to the total of the economy. In addition, it is the sector that generates the most jobs, around 56% (INEC, 2020)